2015
DOI: 10.1002/cmdc.201500131
|View full text |Cite
|
Sign up to set email alerts
|

Freezing the Bioactive Conformation to Boost Potency: The Identification of BAY 85‐8501, a Selective and Potent Inhibitor of Human Neutrophil Elastase for Pulmonary Diseases

Abstract: Human neutrophil elastase (HNE) is a key protease for matrix degradation. High HNE activity is observed in inflammatory diseases. Accordingly, HNE is a potential target for the treatment of pulmonary diseases such as chronic obstructive pulmonary disease (COPD), acute lung injury (ALI), acute respiratory distress syndrome (ARDS), bronchiectasis (BE), and pulmonary hypertension (PH). HNE inhibitors should reestablish the protease–anti-protease balance. By means of medicinal chemistry a novel dihydropyrimidinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 43 publications
3
58
0
Order By: Relevance
“…47 75 Compared to the overall promising rodent DMPK profile of the 3 rd and 4 th generation inhibitors, shows a further improved metabolic stability translating into a low clearance and improved half-life with no inhibitory capacity towards CYP isoforms. 76 Studies with have confirmed an anti-inflammatory and anti-remodeling mode of action in preclinical acute and chronic animal models of ALI, PAH, and PH associated with lung emphysema. 76,[80][81][82] Recently, more research groups from industry have been attracted to 5 th generation inhibitiors, leading to further improvements in potency and metabolic stability (20, 23-25, Table 4; Fig.…”
Section: Th Generation (Pre-adaptive Pharmacophores Derived From 4 Thmentioning
confidence: 88%
See 2 more Smart Citations
“…47 75 Compared to the overall promising rodent DMPK profile of the 3 rd and 4 th generation inhibitors, shows a further improved metabolic stability translating into a low clearance and improved half-life with no inhibitory capacity towards CYP isoforms. 76 Studies with have confirmed an anti-inflammatory and anti-remodeling mode of action in preclinical acute and chronic animal models of ALI, PAH, and PH associated with lung emphysema. 76,[80][81][82] Recently, more research groups from industry have been attracted to 5 th generation inhibitiors, leading to further improvements in potency and metabolic stability (20, 23-25, Table 4; Fig.…”
Section: Th Generation (Pre-adaptive Pharmacophores Derived From 4 Thmentioning
confidence: 88%
“…76 Studies with have confirmed an anti-inflammatory and anti-remodeling mode of action in preclinical acute and chronic animal models of ALI, PAH, and PH associated with lung emphysema. 76,[80][81][82] Recently, more research groups from industry have been attracted to 5 th generation inhibitiors, leading to further improvements in potency and metabolic stability (20, 23-25, Table 4; Fig. 15).…”
Section: Th Generation (Pre-adaptive Pharmacophores Derived From 4 Thmentioning
confidence: 88%
See 1 more Smart Citation
“…1D and 2D NMR spectra were recorded on a Bruker (a.m. 500 MHz) spectrometer (Billerica, MA), using Acetone-d 6 , as solvent and tetramethylsilane (TMS) as an internal standard. Electron ionization (EI) and EI high resolution (HR) mass spectra were obtained on a JEOL JMS-700 instrument (JEOL, Tokyo, Japan).…”
Section: Chemical and Instrumentsmentioning
confidence: 99%
“…Most works have focused on the development of synthetic elastase inhibitors that have high potency (IC 50 in the nanomolar range), show selectivity relative to a panel of other proteases and have good metabolic stability. For instance, the BAY 85-8501 is one of best candidate inhibitors for neutrophil elastase 6,7 . However, there are still relatively few studies disclosing natural products that target this important enzyme 8,9 .…”
Section: Introductionmentioning
confidence: 99%